RANCANGAN APLIKASI KEY PERFORMANCE INDICATOR (KPI) PENILAIAN KINERJA PURCHASING - Dartono Dartono; Dhila Franzely Dhimas Putra; Sumarno Situmeang (Institut Teknologi dan Bisnis (ITB) Swadharma, 2023)
Every company has goals, plans, and dreams about the future of the company. This vision and mission can be achieved if there is a measurement strategy as a measuring tool for achieving the company's vision and mission. Purchasing KPI is assessed from the results of the assignment performance given starting from the assignment of purchase requests, and purchase orders to warehouse receipts put together in one report. This assessment is required regularly, be it annually, every six months, or every three months every month. The goal of this research is to design purchasing performance appraisal applications as a basis for assessing and evaluating performance target achievements. The research method uses qualitative research by collecting data using observation techniques, interviews, and literature study. The results are in the form of a prototype of a performance appraisal application that makes it possible to monitor employee performance. The results of monitoring and assessment will be able to improve employee performance.Setiap perusahaan mempunyai tujuan (goal), rencana (planning) dan impian (dream) tentang masa depan perusahaannya. Visi dan misi ini dapat dilakukan jika adanya strategi pengukuran sebagai alat ukur tercapainya visi dan misi perusahaan. KPI bagian purchasing dinilai dari hasil kinerja penugasan yang diberikan apakah tepat waktu mulai dari penugasan purchase request, purchase order sampai warehouse receipt dijadikan dalam satu report. Penilaian ini dilakukan secara berkala, baik itu per tahun, per enam bulan, per tiga bulan hingga per bulan. Tujuan penelelitian adalah merancang aplikasi penilaian kinerja purchasing sebagai dasar dalam menilai dan mengevaluasi capaian target kinerja. Metode penelitian menggunakan penelitian kualitatif dengan pengumpulan data menggunakan teknik observasi, wawancara dan studi pustaka. Hasil penelitian berupa purwarupa aplikasi penilaian kinerja yang memungkinkan untuk memantau kinerja pengawai dan hasil pemantauan dan penilaian tersebut akan dapat meningkatkan kinerja karyawan.